How accounting and accountants may contribute in sustainability? - Caliskan, Arzu Ozsozgun (EMERALD GROUP PUBLISHING LTD, 2014)
Purpose - The main purpose of this paper is to illustrate the role of accounting and accounting professionals in sustainability by conducting an in-depth literature review. Design/methodology/approach - This is a review-based article that does not contain empirical research. A comprehensive literature research was conducted by using online databases of selected scientific publishers and using keywords such as accounting, accounting professionals, sustainability, sustainability reporting and sustainability accounting. In addition to that, web pages of the accounting regulatory bodies and four big audit companies were also investigated. Findings - Based upon the literature survey, it can be said that there is a lack of defining the relationship between the sustainability concept and accounting and also potential solutions to overcome the problems which create challenges for accounting and accounting professionals. Research limitations/implications - The only limitation of the study can be explained as it being a literature survey. Practical implications - It is expected that the results of the paper will appear in several applications among accounting professionals, the firm that they work in, the association of professional accountants, education institutions and all the stakeholders of accounting, especially in countries with the relatively early stage of sustainability practices. The paper may give insight into aforementioned stakeholders of accounting in reformation of accounting toward sustainability. Originality/value - The main contribution of this paper is to fulfill the gap in the accounting and sustainability literature by suggesting certified sustainability accountant credential that is equipped with core knowledge of environmental engineering as a specialized profession to handle the technical accounting problems that are related to sustainability.
Keywords: Accounting; Sustainability reporting; Accountants; Non-financial reporting; Corporate sustainability; ORGANIZATIONAL-DEVELOPMENT; SYSTEMS; RESPONSIBILITY; Business & Economics